2022
DOI: 10.3390/medicina58111619
|View full text |Cite
|
Sign up to set email alerts
|

External Cephalic Version—A Chance for Vaginal Delivery at Breech Presentation

Abstract: Background and Objectives: In recent years, the rate of caesarean section (CS) has increased constantly. Although vaginal breech delivery has a long history, breech presentation has become the third most common indication for CS. This study aims to identify factors associated with the success of external cephalic version (ECV), underline the success rate of ECV for breech presentation and highlight the high rate of vaginal delivery after successful ECV. Material and Methods: This retrospective observational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
8
1
Order By: Relevance
“…If we could try an ECV with NA for a second attempt after a failed ECV attempt, the success rate and a reduction of Cesarean delivery could be calculated again. In a study performed by Cobec et al [18], the CD rate among participant with successful ECV was 19.4%, while in ours was 6.72%. So, we may attempt to conduct this trial.…”
Section: Discussioncontrasting
confidence: 52%
“…If we could try an ECV with NA for a second attempt after a failed ECV attempt, the success rate and a reduction of Cesarean delivery could be calculated again. In a study performed by Cobec et al [18], the CD rate among participant with successful ECV was 19.4%, while in ours was 6.72%. So, we may attempt to conduct this trial.…”
Section: Discussioncontrasting
confidence: 52%
“…Of these articles, two were from the same team of authors and used the same dataset; Anand et al used the dataset to create a model predicting cephalic position after the ECV, while the Palepu et al created a model to predict vaginal delivery 34,35 . The remaining 11 articles were completely independent from each other; two of these articles proposed two models each 36,37 , while the remaining 9 proposed a single model each [38][39][40][41][42][43][44][45][46] (Figure 2). Two of the articles had an erratum: one was trivial 40,47 and only modi ed a sentence in the abstract, while the other was a correction of a gure describing the decision tree model 41,48 .…”
Section: Relationships Between Articlesmentioning
confidence: 99%
“…The results of the study quality assessment based on the signaling questions are shown in Table 4. Out of 17 new articles, 10 studies were identi ed as having low overall risk of bias and high study quality 22,[33][34][35][36]39,41,[44][45][46] , 6 studies were identi ed as having moderate bias and moderate study quality 29,37,38,42,43,47 , and 1 was considered to have high bias and low quality 30 . This is in addition to Velzel et al's assessment of the 8 prior articles of which 4 were low risk of bias and high study quality and 4 were moderate risk of bias and study quality 10 .…”
Section: Quality and Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these articles, two were from the same team of authors and used the same dataset; Anand et al used the dataset to create a model predicting cephalic position after the ECV, while the Palepu et al created a model to predict vaginal delivery 34,35 . The remaining 11 articles were completely independent from each other; two of these articles proposed two models each 36,37 , while the remaining 9 proposed a single model each [38][39][40][41][42][43][44][45][46] (Figure 2). Two of the articles had an erratum: one was trivial 40,47 and only modified a sentence in the abstract, while the other was a correction of a figure describing the decision tree model 41,48 .…”
Section: Relationships Between Articlesmentioning
confidence: 99%